Enterprise Development: The Role of Enterprise Innovation, Information Technology Convergence on SMEs Performance - Purnomo Mochamad; Irhamni Muhammad Ricza; Azimi Zuhal; Saputra Syafiq Aryanta Manggala; Lase Jayadi (SHS Web of Conferences, 2025)
The study aims to analyze the sustainability of small and medium-sized enterprises (SMEs) through entrepreneurial innovation and information technology convergence in improving SMEs performance. The sample was determined using the Slovin formula, with a total of 99 respondents. Analysis using structural equation models (SEM). The research finds that entrepreneurial innovation and information technology conferencing variables have a positive impact on SME sustainability, and entrepreneurial innovation variables positively affect SME performance, while information technology convergence variables do not have an impact on the performance of SMEs in improving business sustainability. The performance of SMEs has a positive impact that can improve SMEs sustainability. So when SMEs performance increases, it can increase SMEs. The important implications of this research are by using entrepreneurial innovation and information technology, conferencing can enhance the sustainability of small and medium-sized firms.